2012
DOI: 10.1007/978-3-642-33415-3_59
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Scene Flow for Robotic Assisted Minimally Invasive Surgery

Abstract: Information about the 3D shape and motion of tissue surfaces at the surgical site during minimally invasive surgery is important for providing metric measurements that enable the deployment of image-guidance and enhanced robotic control. This article presents a scene flow algorithm that recovers the deformation and 3D structure of the surgical field-of-view from stereoscopic images by propagating information starting from a sparse set of candidate seed matches. By imposing spatial and temporal constraints the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 19 publications
(37 reference statements)
1
47
0
Order By: Relevance
“…The proposed algorithm is quantitatively evaluated by two cardiac datasets collected from [14] which have an associated registered CT model as ground truth as shown in Fig. 3.…”
Section: Cardiac Phantom Experimentsmentioning
confidence: 99%
“…The proposed algorithm is quantitatively evaluated by two cardiac datasets collected from [14] which have an associated registered CT model as ground truth as shown in Fig. 3.…”
Section: Cardiac Phantom Experimentsmentioning
confidence: 99%
“…Another technique also operating at near real-time frame rates that uses local optimization to propagate disparity information around correspondence seeds obtained using feature matching as developed in (Stoyanov et al, 2005b) has also been shown to perform well for endoscopic images . This method has the desirable property of ignoring regions with highlights, occlusions or high uncertainty and has also recently been extended to recover temporal motion as well as 3D shape (Stoyanov, 2012a). An extension of the algorithm showing reduced noise artefacts has also been presented (Bernhardt et al, 2012).…”
Section: Application To Laparoscopymentioning
confidence: 99%
“…(e) Disparity image obtained using the images in (b) and (c) with the algorithm reported in where lighter colours are closer to the camera. (f) 3D motion of the surface in images (b) and (c) obtained between two time frames using stereoscopic scene flow where warmer colours represent larger motion (Stoyanov, 2012a). (g) An overlay of the stereoscopic image pair illustrating parallax between the stereo views.…”
Section: Introductionmentioning
confidence: 99%
“…4 to mimic the periodic deformation of the tissue surface induced by the cardiac cycle and respiration [23]. The environment can generate synthetic image sequences by performing small but arbitrary rotations and translations to the pixels of one template image.…”
Section: Synthetic Data Experimentsmentioning
confidence: 99%